The Effect Of Tomato Extract (Solanum lycopersicum L.) and Coconut Water (Cocos nucifera L.) as Growth Regulators (PGR) in Murashige And Skoog (Ms) Media on the Growth of In Vitro Crossed Cattleya Orchid Tissue Culture - Hanny Putri Satiyanto; Ruly Budiono; Asep Zainal Muttaqin (International Journal of Quantitative Research and Modeling, 2026)
Cattleya orchids are highly prized ornamental plants that can be significantly propagated using in vitro tissue culture techniques. PGRs significantly influences the success of tissue culture. Synthetic PGRs are commonly used, but are relatively expensive and not environmentally friendly, so natural materials need to be used as alternatives. The purpose of this study was to determine how tomato extract (Solanum lycopersicum L.), coconut water (Cocos nucifera L.), and their combination as natural PGRs affect the growth of hybrid Cattleya orchid plantlets on Murashige and Skoog (MS) media. A Completely Randomized Design (CRD) was used to treat tomato extract (0%; 1%; 1.5%; 2%; 2.5%) and coconut water (0%; 5%; 10%; 15%; 20%) and their combinations. This study analyzed data based on parameters of plantlet height, number of leaves, number of roots, root length, and wet weight using ANOVA analysis followed by Duncan's test at the 5% level. The results showed that several growth parameters were affected such as plantlet height, number of roots, root length, and fresh weight showed significant effects. The number of leaves did not have a significant effect. Natural PGRs are generally considered a more cost-effective and environmentally friendly alternative, their effectiveness has not completely replaced synthetic PGRs.